Plant Components Exhibit Pharmacological Activities and Drug Interactions by Acting on Lipid Membranes - Tsuchiya, Hironori; Mizogami, Maki (Pharmacognosy Communications)
In light of a novel mode of action on lipid membranes, we studied pharmacological activities of representative medicinal plant components, flavonoids, and verified their possible interactions with membrane-acting drugs. Fluorescence polarization measurements with different probes revealed that 1–500 μM phytochemicals structure dependently acted on biomimetic membranes prepared with phospholipids and cholesterol to change the membrane physicochemical property, fluidity, by preferentially acting on the deeper regions of lipid bilayers. In the structure and membrane activity relationship characterized, greater potencies to decrease membrane fluidity were associated with the polyphenol structures, flavonoids with hydroxyl groups at the 3-, 3’-, 4’-, 5-, 5’- and/or 7-position. Quercetin and (–)-epigallocatechin gallate, meeting the structural requirements, effectively inhibited at 1–10 μM the proliferation of tumor cells to show 74.3–75.5% inhibition after 48 h culture and the membrane lipid peroxidation induced by 10 μM peroxynitrite to show 96.8–100% inhibition. These antiproliferative and antioxidant flavonoids also changed the fluidity of cell membranes simultaneously with exhibiting pharmacological activities. The membrane action is, at least in part, mechanistically responsible for the disease preventive and therapeutic effects of medicinal plants containing flavonoids. The selected membrane-active phytochemicals, phloretin and capsaicin antagonistically or additively influenced at 25– 500 μM the membrane-fluidizing effects of lidocaine and bupivacaine of clinically relevant concentrations. These results suggest that medicinal plant components may cause inhibitory or cooperative drug interactions with local anesthetics which act on lipid bilayers to modify the membrane environments for Na + and K + channels embedded in biomembranes.
Keywords: antioxidant; antiproliferative; lipid bilayer; local anesthetic; membrane fluidity; flavonoid